Surgical Outcomes of Endoscopic Transsphenoidal Pituitary Adenoma Resection in Elderly Versus Younger Patients - Alexander, Tyler D.; Chitguppi, Chandala; Collopy, Sarah; Murphy, Kira; Lavergne, Pascal; Patel, Prachi; Khoury, Tawfiq; Rabinowitz, Mindy; Nyquist, Gurston G.; Rosen, Marc R.; Farrell, Christopher J.; Karsy, Michael; Evans, James J. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Introduction Pituitary adenomas (PAs) are one of the most common types of intracranial neoplasm with increased incidence in elderly patients. The outcomes of endoscopic transsphenoidal surgery (ETS) specifically on elderly patients remain unclear.Methods We performed a retrospective cohort study to compare elderly patients (age ≥65 years) with nonelderly patients (age <65 years) who underwent ETS for PA from January 2005 to December 2020. Surgical outcomes, including extent of resection, complication profile, length of stay, and endocrinopathy rates, were compared between elderly and nonelderly patients.Results A total of 690 patients were included, with 197 (29%) being elderly patients. Elderly patients showed higher rates of hypertension (p < 0.05), myocardial infarction (p < 0.01), and atrial fibrillation (p = 0.01) but not other comorbidities. Elderly patients also had more frequent optic nerve involvement (72 vs. 61% of cases, p = 0.01). Tumor characteristics and other patient variables were otherwise similar between younger and elderly patients. Postoperative cerebrospinal fluid (CSF) leaks (2 vs. 2%, p = 0.8), 30-day readmission, reoperation, postoperative complications, and postoperative endocrinopathies were similar between younger and older patients. Subdividing patients into age <65, 65 to 79, and >80 years also did not demonstrate a worsening of surgical outcomes with age.Conclusion For well-selected elderly patients in experienced endoscopic skull base centers, good surgical outcomes similarly to younger patients may be achieved.
Keywords: elderly; pituitary adenoma; outcomes; endonasal; transsphenoidal